2018
DOI: 10.1038/s41598-018-26395-4
|View full text |Cite
|
Sign up to set email alerts
|

One-way edge modes in a photonic crystal of semiconductor at terahertz frequencies

Abstract: Electromagnetic edge mode in a photonic crystal (PhC), which is a square array of semiconductor rods in air, is theoretically investigated for terahertz frequencies. In the PhC, gyroelectric anisotropy is introduced in the semiconductor rods by applying an external magnetic field and consequently, a degeneracy point, at which two dispersion surfaces intersect, is lifted and a new band gap is created. The edge mode sustained by the PhC possesses the character of one-way propagation, and it even can be immune to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…the magnetic field is parallel to the external magnetic field), where k 0 is the vacuum wavenumber and v e is the Voigt permittivity, which is defined by . The value of v e is found to be 0.23 for f 3.1 THz = [20]. The bulk modes for the E polarization (i.e.…”
Section: Physical Model and Numerical Solutionmentioning
confidence: 86%
See 2 more Smart Citations
“…the magnetic field is parallel to the external magnetic field), where k 0 is the vacuum wavenumber and v e is the Voigt permittivity, which is defined by . The value of v e is found to be 0.23 for f 3.1 THz = [20]. The bulk modes for the E polarization (i.e.…”
Section: Physical Model and Numerical Solutionmentioning
confidence: 86%
“…As the band gap of a PhC is adjustable by properly changing the lattice constant, one-way edge modes in PhCs have a remarkable advantage over the one-way SMPs. Very recently, it has been reported that a terahertz one-way edge mode can be realized in the PhC which is an array of semiconductor rods in air, and the operation range lies outside the band gap of the semiconductor itself [20]. In the present paper, a new type of PhC which operates at terahertz frequencies is proposed and investigated theoretically.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…18 experimentally observed an interference-induced transparency effect in InSb, which shows its good magnetic tunability in the THz regime. Shen’s group proposed the broadband THz one-way transmission based on the MO photonic crystal and MO plasmonic structures 19,20 . Recently, we also experimentally reported a THz nonreciprocal circular dichroism and Faraday effect of over 90° rotation angle under a weak magnetic field 20 , which can be used as THz MO polarization convertor and modulator.…”
Section: Introductionmentioning
confidence: 99%
“…ge states exist e reversal sym ry for the gyro cal or microwa in semiconduc h a relatively s gical devices b osed [25]. Sim al [26].…”
Section: Introductionmentioning
confidence: 99%